Soluble inflammatory biomarkers and apolipoprotein A1 gene variants in low high density lipoprotein concentration / Nurul Atiqah Mohd Mokhsin - Mohd Mokhsin, Nurul Atiqah (2016)
Atherosclerosis leads to coronary artery disease (CAD) is a main cause of death worldwide. Low High density lipoprotein (HDL-c) concentration has been associated with increased inflammation, which causes increase risk of CAD. Nevertheless, inflammatory status of low HDL-c subjects and primary causes due to variations of the apolipoproteinAl (APOA1) gene involved in HDL-c metabolism have not been extensively studied. Hence, this study compared serum concentration of inflammatory biomarkers [interleukin (IL)-6 and high sensitivity c-reactive protein (hsCRP)] between low HDL-c subjects and matched controls, studied the association between HDL-c and inflammatory biomarkers concentrations, determined if HDL-c is an independent predictor of inflammatory biomarkers, and identified variations of the APOA1 gene in low HDL-c subjects compared with matched controls. This study consisted of two parts; biochemical and genetic association studies. Two hundred and seven (207) low HDL-c subjects and 215 matched controls were recruited in the biochemical study, while 70 low HDL-c subjects and 140 matched controls were included in the genetic association study. Serum and whole blood samples were collected for analysis of biochemical and genetic association studies respectively. The results showed enhanced inflammatory biomarkers in low HDL-c subjects, and inverse association was discovered between HDL-c and inflammatory biomarkers, as well as HDL-c was an independent predictor for IL-6. Furthermore, four variants of APOA1 gene were significantly associated with low HDL-c concentration. In conclusion, low HDL-c concentration is strongly correlated to the enhanced inflammatory biomarkers, whereas APOA1 gene may play an important role in low HDL-c subjects in this study.